2016
DOI: 10.1177/0956462415605232
|View full text |Cite
|
Sign up to set email alerts
|

CURB-65 and other markers of illness severity in community-acquired pneumonia among HIV-positive patients

Abstract: As the relative burden of community-acquired bacterial pneumonia among HIV-positive patients increases, adequate prediction of case severity on presentation is crucial. We sought to determine what characteristics measurable on presentation are predictive of worse outcomes. We studied all admissions for community-acquired bacterial pneumonia over one year at a tertiary centre. Patient demographics, comorbidities, HIV-specific markers and CURB-65 scores on Emergency Department presentation were reviewed. Outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The PSI score of the patient was an independent predictor of mortality but CURB_65 was not a good predictor of mortality. 15,16 In conclusion, the early prediction of the mortality risk is important to determine the high risk patients to hospitalize in intensive care unit and close follow up. But when we look at the mortality rates in each CURB_65 score, the mortality rates are increasing while CURB_65 score is increasing ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PSI score of the patient was an independent predictor of mortality but CURB_65 was not a good predictor of mortality. 15,16 In conclusion, the early prediction of the mortality risk is important to determine the high risk patients to hospitalize in intensive care unit and close follow up. But when we look at the mortality rates in each CURB_65 score, the mortality rates are increasing while CURB_65 score is increasing ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…14 Also some other studies reported that the higher the CURB_65 score the higher the mortality. 15,16 In conclusion, the early prediction of the mortality risk is important to determine the high risk patients to hospitalize in intensive care unit and close follow up. The lactate level, PSI score and CURB_65 scores are good predictors for mortality.…”
Section: Figu Re 1 Roc Curve Of Lactate Level For Mortalitymentioning
confidence: 99%
“…The study by Albrich et al (42), which analyzed the association between nasopharyngeal S. pneumoniae densities in HIV-infected patients from South Africa with markers of severity and poor outcomes, reported no correlation between CURB-65 and mortality in these patients. However, the study by Almeida et al (62) investigated the use of CURB65 in HIV-infected patients, and reported that a higher A c c e p t e d M a n u s c r i p t CURB65 score and a CD4 count lower than 200 cells/mL were both associated with worse outcomes. They concluded that the CURB65 score plus CD4 cell count could be used in HIV-infected patients with CAP.…”
Section: Assessment Of Severity and Making Site-of-care Decisionsmentioning
confidence: 99%
“…We recommend that such patients do not need treatment, admission, or care sites that differs from that of the general population. 13,14,15,17,18,19,20,22,23,24,25,27,28,29,30,62,63,66,67,68,70,71 A c c e p t e d M a n u s c r i p t…”
Section: Five-year Viewmentioning
confidence: 99%
“…Similar findings were found by Almeida et al in 49 PLWH admitted with pneumonia in an emergency department with a median CRB65 score lower then HIV-negative patients but which were also associated with a higher risk of mortality. 37 In the paper of Yone et al, 54 out 62 PLWH admitted with community acquired pneumonia (CAP) had CRB65 of 0-1. 38 In our study, adding the pulse oximetry to CRB-65 score, as suggested by the Consensur II, the Latin America Pneumonia working Group, increased the ability to confidently predict the 30-day in-hospital mortality.…”
Section: Discussionmentioning
confidence: 99%